Degree of Grammaticalisation of Behind, Beneath, Between and Betwixt in Middle English - Ciszek-Kiliszewska, Ewa (Research in Language, 2018)
The present paper traces the history of four selected adverbs with the prefix be- in Middle English. Already in Old English behind, beneath, between and betwixt are attested to function as both adverbs and prepositions, which demonstrates that the process of grammaticalisation accounting for the development of prepositions from adverbs started before that period. The focus of the study are the diachronic changes of the degree of grammaticalisation of the examined lexemes in the Middle English period as demonstrated by the ratio of their use with a respective function in the most natural context. Hence, specially selected Middle English prose texts are analysed. The analysis shows that while behind and beneath are still frequently used as adverbs in the whole Middle English period, between and betwixt are predominantly used as prepositions already in Early Middle English. This clearly demonstrates that the degree of grammaticalisation of the latter two Middle English words was much higher than that of behind and beneath.